2024
DOI: 10.3389/fendo.2024.1304188
|View full text |Cite
|
Sign up to set email alerts
|

Deep response to a combination of mTOR inhibitor temsirolimus and dual immunotherapy of nivolumab/ipilimumab in poorly differentiated thyroid carcinoma with PTEN mutation: a case report and literature review

Youjin Oh,
Joo Hee Park,
Trie Arni Djunadi
et al.

Abstract: Treating advanced thyroid cancer presents challenges due to its resistance to various treatment modalities, thereby limiting therapeutic options. To our knowledge, this study is the first to report the efficacy of temsirolimus in conjunction with dual immunotherapy of nivolumab/ipilimumab to treat heavily treated advanced PDTC. A 50-year-old female initially presented with a rapidly enlarging mass on her right neck. Subsequent diagnosis revealed poorly differentiated thyroid carcinoma, leading to a total thyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 42 publications
(66 reference statements)
0
7
0
Order By: Relevance
“…Since cytological diagnosis of PDTC based on FNAC is challenging, our review has shown that some patients underwent a hemithyroidectomy or subtotal thyroidectomy with a completion thyroidectomy after histological diagnosis [ 38 , 44 , 52 , 54 , 59 , 65 , 69 , 85 , 103 , 104 , 107 , 108 , 115 , 117 ], but the majority of them were submitted to a total thyroidectomy as the initial operation [ 40 , 41 , 42 , 43 , 46 , 48 , 49 , 50 , 51 , 53 , 54 , 55 , 56 , 58 , 60 , 61 , 62 , 64 , 67 , 68 , 69 , 72 , 73 , 75 , 79 , 80 , 81 , 82 , 85 , 86 , 88 , 89 , 90 , 91 , 92 , 93 , 95 , 96 , 100 , 101 ,…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Since cytological diagnosis of PDTC based on FNAC is challenging, our review has shown that some patients underwent a hemithyroidectomy or subtotal thyroidectomy with a completion thyroidectomy after histological diagnosis [ 38 , 44 , 52 , 54 , 59 , 65 , 69 , 85 , 103 , 104 , 107 , 108 , 115 , 117 ], but the majority of them were submitted to a total thyroidectomy as the initial operation [ 40 , 41 , 42 , 43 , 46 , 48 , 49 , 50 , 51 , 53 , 54 , 55 , 56 , 58 , 60 , 61 , 62 , 64 , 67 , 68 , 69 , 72 , 73 , 75 , 79 , 80 , 81 , 82 , 85 , 86 , 88 , 89 , 90 , 91 , 92 , 93 , 95 , 96 , 100 , 101 ,…”
Section: Discussionmentioning
confidence: 99%
“…Unlike in DTC [ 123 , 124 ], RAI appears to be relatively ineffective in the control of distant metastases in PDTC; thus, it is reasonable to consider the use of RAI for metastatic/advanced disease that demonstrates definite iodine uptake [ 125 , 126 ]. Likewise, most cases in our review received at least one cycle of RAI treatment, even without detectable metastatic foci [ 38 , 39 , 40 , 41 , 42 , 43 , 46 , 48 , 49 , 50 , 51 , 53 , 54 , 55 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 73 , 74 , 75 , 80 , 81 , 82 , 85 , 86 , 87 , 88 , 90 , 91 , 97 , 99 , 101 , 102 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 ...…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations